Physical-chemical influences and cell behavior of natural compounds on titanium dental surfaces - Maquera-Huacho, Patricia Milagros [UNESP]; Garcia de Carvalho, Gabriel [UNESP]; Júnior, Miguel Jafelicci [UNESP]; Junior, Elcio Marcantonio [UNESP]; Palomari Spolidorio, Denise Madalena [UNESP] (FapUNIFESP (SciELO), 2023)
The present study evaluated the influence of carvacrol, terpinene-4-ol, and chlorhexidine on the physical-chemical properties of titanium surfaces, cell viability, proliferation, adhesion, and spreading of fibroblasts and osteoblasts in vitro. Titanium surfaces (Ti) were treated with Carvacrol (Cvc), Terpinen-4-ol (T4ol), Chlorhexidine (CHX), DMS0, and ultrapure water (Control group). Physical-chemical modifications were evaluated by surface wettability, the surface free energy (SFE) calculated from the contact angle values using the Owens-Wendt-Rabel-Kaeble (0WRK) equation, scanning electron microscopy (SEM) and energy dispersive spectrometry probe (EDS) system. Cells were seeded onto Ti-treated surfaces and incubated for 24 h and 72 h, then evaluated by Alamar blue assay and fluorescence microscopy. Surfaces treated with Cvc and T4ol showed the presence of Na, O, and CL All surfaces showed hydrophilic characteristics and SFE values between 5.5 mN/m and 3.4 mN/m. On the other hand, EDS peaks demonstrated the presence of O and Cl after CHX treatment. A reduction of cell viability and adhesion was noted on titanium surfaces treated with CHX after 24 and 72h. In conclusion, the results indicate that the decontamination with Cvc and T4ol on Ti surfaces does not alter the surface proprieties and allows an adequate interaction with cells involved in the re-osseointegration process such as fibroblasts and osteoblasts.
Keywords: Chlorhexidine; Dental Implants; Fibroblasts; in vitro; Natural compounds; Osteoblasts; Surface Properties